Synthesis of the methods of research of stability of the electric drive “thyristor voltage converter – induction motor - Boyko, Andrew; Besarab, Oleksandr; Semeniuk, Vladimir; Naydenko, Elena (Eastern-European Journal of Enterprise Technologies, 2016)
In the open-loop systems of electric drive (ED) «Thyristor voltage converter − induction motor (TVC−IM) on the working section of mechanical characteristics, in some cases, the oscillations of the output values can be recorded. Such unstable modes are considered to be a negative phenomenon, which may limit the use of ED and is subject to detailed study. The transfer function of electromagnetic part of an induction motor was determined, which characterizes the transient function of an electromagnetic torque. It is proved that for different motors the character of the changes in the torque varies, the necessity of selecting specific components of electromagnetic torque was substantiated. Based on the received transfer function, the synthesis of computational−analytical method of the study of the stability of the open-loop system of electric drive of TVC−IM was conducted. The analysis of stability was carried out with different induction motors of one series based on a simplified method by simulations and experiments. The assessment of the impact of different factors on the stability was made, namely: the IM parameters, load torques, the values of the angles of switching valves and initial electromagnetic conditions. It is shown that the study of the ratios of time constants of transient function of electromagnetic torque of IM and electromechanical time constants allows forecasting the possibility of the occurrence of oscillations. The analysis of influence of schematic configurations of pulse-phase systems of control of the TVC on the character of unstable modes was carried out. The results of this work make it possible to qualitatively and quantitatively characterize a mode of oscillations of TVC−IM, while also to determine the area of possible unstable performance, as well as to attempt to eliminate the preconditions to the occurrence of oscillability.